2022
DOI: 10.1016/j.techsoc.2021.101845
|View full text |Cite
|
Sign up to set email alerts
|

Mobile internet adoption in West Africa

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…This implies that agricultural production and marketing activities that is dealt with these digital technologies work well and fulfil their requirements. Although a number of studies (Ammann et al, 2022; Granguillhome Ochoa et al, 2022; Kendall et al, 2022; Kernecker et al, 2020) have looked at farmers’ perception of digital technologies in agriculture in both developing and developed economies, the effectiveness of the internet and connectivity/wireless, mobile applications and digital platforms in dealing with farming activities as perceived by smallholder farmers is rarely discussed. It became apparent that the adoption of the internet and connectivity/wireless, mobile applications and digital platforms was negatively related with smallholder farmers’ age and this relationship was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that agricultural production and marketing activities that is dealt with these digital technologies work well and fulfil their requirements. Although a number of studies (Ammann et al, 2022; Granguillhome Ochoa et al, 2022; Kendall et al, 2022; Kernecker et al, 2020) have looked at farmers’ perception of digital technologies in agriculture in both developing and developed economies, the effectiveness of the internet and connectivity/wireless, mobile applications and digital platforms in dealing with farming activities as perceived by smallholder farmers is rarely discussed. It became apparent that the adoption of the internet and connectivity/wireless, mobile applications and digital platforms was negatively related with smallholder farmers’ age and this relationship was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that agricultural production and marketing activities that is dealt with these digital technologies work well and fulfil their requirements. Although a number of studies (Ammann et al, 2022;Granguillhome Ochoa et al, 2022;Kendall et al, 2022;Kernecker et al, 2020) have looked at farmers' perception of digital technologies in agriculture in both developing and developed economies, the effectiveness of the internet and connectivity/wireless, mobile applications and digital platforms in dealing with Interestingly, it has been found that the adoption of the internet and connectivity/wireless, mobile applications and digital platforms was positively and significantly linked with scientist interactions, which means that smallholder farmers who had interactions with scientists (experts/researchers/lecturers in agronomy, economics and engineering) were in a better position to adopt the digital technologies than those who did not interact with these people. This could be attributed to the fact that smallholder farmers who often interact with scientists may receive more information about which digital technologies are most appropriate to smallholders' farms as well as knowledge/ support in applying the digital technologies on their farms, and this may affect their decision regarding the adoption of the digital technologies.…”
Section: Factors Affecting Smallholder Farmers' Use Of Digital Agricu...mentioning
confidence: 99%
“…Thus, a lack of basic literacy is a barrier to digital inclusion, as most services and devices are designed for people who can read and write. Furthermore, knowledge of English or French is positively associated with greater digital inclusion, which can be explained by the greater availability of internet content in these languages (Ochoa et al, 2022;Pénard et al, 2012Pénard et al, , 2015.…”
Section: Determinants Of Digital Divides In Sub-saharan Africa At The...mentioning
confidence: 99%
“…More generally, because literacy and other digital skills are necessary to fully use and benefit from digital technologies, educational attainment appears to be a key determinant of digital inequalities (Birba & Diagne, 2012;Deen-Swarray, 2016;Forenbacher et al, 2019;Hasbi & Dubus, 2020;Ochoa et al, 2022;Pénard et al, 2012Pénard et al, , 2015.…”
Section: Determinants Of Digital Divides In Sub-saharan Africa At The...mentioning
confidence: 99%
“…It is also a factor between countries, as poorer nations lack infrastructure, skills and scale to gather much data, and the institutional resources to regulate it and build trust (World Bank, 2021). For instance, sub-Saharan African nations' welfare services struggled to identify their poorest citizens during the COVID-19 pandemic because they simply had not been able to afford effective data collection and retrieval prior to the emergency (Gelb and Mukherjee, 2020;Rogger and Somani, 2018), and Internet penetration levels were some of the lowest in the world (Granguillhome Ochoa et al, 2022). The government of…”
Section: A Note On Western-centrismmentioning
confidence: 99%